Developing new approaches for transcriptomics and genomics: using major resources developed in model species for research in crop species - Chai, Hui Hui (2014)
With the estimated increase in global demand for food and over-reliance on staple food crops, the exploitation of agricultural biodiversity is important to address food security challenges. The aim of this study is to develop approaches to transfer major informational and physical resources developed in model plant and major crop species to resources poor crop species, using oil palm and Bambara groundnut as two exemplar crops. XSpecies (cross-species) approach, the core approach of the study, is described as the approach which uses microarrays developed for a given species to analyse another related species. The use of the XSpecies approach (here the cross-hybridisation of DNA from oil palm onto heterologous Affymetrix microarrays for Arabidopsis and rice), is the first experiment reported in oil palm and focused on a bulked segregant analysis of different shell-thicknesses for oil palm fruit. Primers design involved screening candidate probe-pairs filtered using PIGEONS software against oil palm transcriptome sequences generated using 454 sequencing technology. The results provided an insight into the effects of sequence divergence between oil palm and the reference species (Arabidopsis and rice) onto the power of detecting single feature polymorphism (SFPs) in oil palm, implying the importance of close association between studied and model plant/crop in XSpecies approach. The XSpecies approach coupled with genetical genomics was also tested within legumes, with Bambara groundnut as the query species compared to soybean as the resource rich species (20 Mya). A mild drought experiment, conducted in a controlled environment glasshouse, used an F5 segregating population derived from a controlled cross between DipC and Tiga Nicuru in Bambara groundnut. The cross-hybridisation of Bambara groundnut leaf RNA to the soybean GeneChip individual oligonucleotide probes resulted in a total of 1,531 of good quality gene expression markers (GEMs) on the basis of the differences in the hybridisation signal strength. The first ‘expression-based’ genetic map (GEM map) was constructed using 165 GEMs spanning 920.3 cM of Bambara groundnut genome. The first high density DNA-marker genetic map of 1,341.3 cM combining dominant DArT and co-dominant SNPs, developed using the DArT Seq approach, with additional pre-existing microarray-based DArT and SSR markers, was also developed in the F3 segregating population. Both maps were combined to form the first integrated map of 1,250.7 cM with 212 markers. Morphological differences and the rapid reduction in stomatal conductance observed within the F5 segregating population in the drought experiment provided trait data for a QTL analysis. The comprehensive QTL analysis in Bambara groundnut detected significant QTLs for morphological traits using GEM map, including internode length, peduncle length, pod number per plant, pod weight per plant, seed number per plant, seed weight per plant, 100-seed weight, shoot dry weight and harvest index across four linkage groups: LG1, LG2B, LG8B and LG11A. The loci controlling internode length and peduncle length were also consistently mapped to single marker on LG1 in DArTseq map using F3 segregating population, suggesting that these two traits are probably controlled by single gene or two closely linked genes. Despite significant genotypes effects on stomatal conductance tested in ANOVA analysis, no major QTLs were detected, suggesting the contributions of a number of small genetic effects to stomatal conductance. A preliminary homology search using the LG1 linkage group markers and associated gene models showed the ability to develop a framework for identification of candidate genes in Bambara groundnut relative to soybean. The present study also developed the resources for an eQTL analysis in a cross-species context. Translation from major and model plant species to underutilised and resource poor crops is critical to be able to develop many crop species with potential for future agriculture. This study examines some of the approaches which might be adopted and replicated in various underutilised crop species.